The Mediating Effect of e-Satisfaction and Trust on the Influence of Brand Image and e-Loyalty - Giovano Melvernus Hendrawan; Maria Yosephine Dwi Hayu Agustini (Soegijapranata Catholic University, 2021)
Loyalty to an e-commerce is difficult to be gained even though factors influencing it have been studied by many. Among others, brand image, e-satisfaction, and trust are the factors. This study aims at analyzing mediating effect of e-satisfaction and trust on the influence of brand image and e-loyalty in the case of Tokopedia, an e-marketplace with strong brand image in Indonesia. Questionnaires to 114 buyers who are categorized as generation Y and Z were distributed using Google form. The Mediating Regression Analysis (MRA) test was applied to see mediating effect of e-satisfaction and trust. The data were tested for their normality, multicollinearity, and heteroscedasticity before the regression. The results indicate only brand image and e-satisfaction that affect e-loyalty positively and significantly. E-satisfaction is also found to mediate brand image and e-loyalty. Since trust is insignificantly affect e-loyalty, it thus does not mediate brand image and e-loyalty.